2022
DOI: 10.1111/jog.15484
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual disorders: Premenstrual syndrome and premenstrual dysphoric disorder

Abstract: Recently, the term premenstrual disorders (PMDs), which includes premenstrual syndrome and premenstrual dysphoric disorder as a continuum, has been proposed. Although the precise etiology of PMDs remains unknown, the involvement of hormonal fluctuations is clear. The brain transmitters, serotonin and γ-amino butyric acid, also seem to be involved. Serotonin reuptake inhibitors and oral contraceptives are the current mainstay of treatment, but these are insufficient. Even the currently used prospective twoperio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 96 publications
0
18
0
1
Order By: Relevance
“…The exact pathophysiology of PMDs remains unclear; however, the effectiveness of selective serotonin reuptake inhibitors (SSRIs) as therapeutic agents is reportedly related to the brain transmitter serotonin. 11 Experiments using rat models of social isolation have reported that the serotonin 1A receptor agonist buspirone and the SSRI fluoxetine improve behavioral abnormalities caused by isolation. 38 From this, isolation and loneliness can be inferred to be associated with serotonin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact pathophysiology of PMDs remains unclear; however, the effectiveness of selective serotonin reuptake inhibitors (SSRIs) as therapeutic agents is reportedly related to the brain transmitter serotonin. 11 Experiments using rat models of social isolation have reported that the serotonin 1A receptor agonist buspirone and the SSRI fluoxetine improve behavioral abnormalities caused by isolation. 38 From this, isolation and loneliness can be inferred to be associated with serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…Premenstrual symptoms are typical of these symptoms; specifically, they consist of a variety of mood, behavioral, and physical symptoms specific to the late luteal period. 10 , 11 Premenstrual disorders (PMDs) consist of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) (a severe form of PMS with predominantly mental symptoms). 12 These are the pathological conditions associated with premenstrual symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1950s, the term premenstrual syndrome (PMS) was introduced for physical and psychological symptoms occurring within 2 weeks before menses, with relief occurring after the onset of the menstrual period [ 1 3 ]. According to the American Congress of Obstetricians and Gynecologists (ACOG), the diagnostic criteria for PMS include somatic symptoms, such as abdominal bloating, breast tenderness or swelling, headache, joint or muscle pain, swelling of the extremities, and weight gain, as well as mental symptoms, including angry outbursts, anxiety, confusion, depression, irritability, and social withdrawal [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) are characterized by unpleasant mental and physical symptoms that significantly impair the quality of life 1 . In Japan, the social recognition of PMS/PMDD lags behind that of other countries, and treatment for these disorders is not widely available.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, OCs/LEPs containing drospirenone have been verified for their therapeutic effects on PMDD and are considered one of the standard treatments, including PMS 2,4 . In Japan, Kampo, a Japanese herbal medicine, is universally used for treatment 1 . Although obstetricians, gynecologists (OB/GYNs), and psychiatrists are the main providers of PMS/PMDD treatment in Japan, the actual status of the diagnostic and treatment methods used remains unknown.…”
Section: Introductionmentioning
confidence: 99%